Baseline clinical predictors of an ultimate giant cell arteritis diagnosis in patients referred to temporal artery biopsy. Issue 7 (July 2016) - Grossman, Chagai; Barshack, Iris; Koren-Morag, Nira; Ben-Zvi, Ilan; Bornstein, Gil
Abstract The diagnosis of giant cell arteritis (GCA) is based on clinical grounds and confirmed by characteristic histological findings on temporal artery biopsy (TAB). Patients may be diagnosed with GCA based on clinical grounds only, despite negative histological findings. We aimed to investigate which baseline clinical and laboratory features best predict an ultimate diagnosis of giant cell arteritis among patients referred to TAB. We retrospectively analyzed 224 patients who underwent TAB in our hospital between 2000 and 2014. Patients were diagnosed with GCA if TAB was positive for GCA, or by clinical grounds only despite a negative biopsy, provided they fulfilled the American College of Rheumatology 1990 criteria. Baseline clinical and laboratory features were obtained from medical records. Predictors of an ultimate GCA diagnosis were investigated. Overall, 82 patients were diagnosed with GCA—57 had histological evidence of GCA and 25 were diagnosed with GCA despite a negative biopsy. One hundred and forty-two patients were not diagnosed with GCA. Predictors of an eventual diagnosis of GCA in a multivariate logistic regression analysis were headache (OR = 6;p < 0.001), jaw claudication (OR 4.5;p = 0.007), erythrocyte sedimentation rate (ESR) (OR = 1.5;p = 0.032) and platelet count (OR = 1.74;p = 0.004). Among patients referred to TAB, headache, jaw claudication, ESR, and thrombocyte levels are predictors for an ultimate diagnosis of GCA. These clinical and laboratory features should be considered when contemplating the diagnosis and treatment of GCA.